New directions in agri-environmental governance: Re-assembling food, knowledge and autonomy - (:unkn) unknown (My University, 2025)
This project builds on the observation that current schemes for agri-environmental governance (AEG) are failing to answer new challenges posed by environmental pressures such as natural resource depletion and global warming (Marsden, 2013). In their studies of Western industrialised countries, agri-food scholars have mainly addressed these issues in two ways: first, they have focused on farmers’ resistance to agri-environmental policies; second, they have examined the difficulties faced by projects to create small-scale or alternative food networks that attempt to transform the dominant unsustainable food regime. My own work has explored each of these issues in turn (Forney, 2010 ; 2012a ; Forney & Haeberli, 2014 ; Forney & Stock, 2014), demonstrating their relevance but also the blind-spots and limits imposed by a narrow focus on farmers and by a truncated understanding of “alternatives”. Building on this work, the current project sets out to incorporate these two issues into a broader analytic framework. More precisely, I identify three dimensions of AEG as potentially opening up new paths towards more sustainable governance practices: reconnection with food production, collective creation and recognition of knowledge, and emerging possibilities for farmer autonomy. At the most general level, these three dimensions will serve both as a guide for assessing a large panel of AEG instruments in several national contexts (Switzerland, New Zealand, and the United Kingdom) as well as at the transnational level, and as concepts that can help us rethink current policies and propose new orientations for legislation and policy-making. The project is structured around three axes: • First, I will propose a preliminary typology of a wide spectrum of AEG instruments, focusing on their multiple “modes of governance” (Olivier de Sardan, 2010), or, in other words, on the social logics and processes they draw on. • Second, I will test this typology through a series of ethnographic case studies. These case studies will detail AEG practices resulting from the implementation of AEG instruments in varying contexts and within different networks. Specific attention will be paid to the design of AEG instruments, focusing on the actors involved, their roles and objectives, the tools and metrologies used in control and assessment procedures, and the relations between AEG instruments. These in-depth case studies will also allow me to understand how actors become enrolled in AEG networks and what consequences this participation has for their daily practices and lived experience. • Third, these case studies will serve as the basis for an analytic and prospective exploration of the transformative potential of AEG practices, looking at how they alter the assemblage and dynamics of the networks in which they develop. As mentioned, three central issues within these networks – food, knowledge and autonomy – will serve as key analysers of potential to engage with deeper change towards more sustainable food systems. The added value of this approach lies in its rigorous use of an anthropological perspective that will allow me to cut across established categories of analysis in order to focus ethnographically on governance practices and on the social uses of governance instruments “on the ground”. The ultimate objective of this research is to produce an encompassing theoretical framework for the analysis of AEG. Thus, our results will not only contribute significantly to academic research on AEG and agri-food system sustainability, they will also provide valuable insights and recommendations for the development of socially and culturally appropriate AEG instruments, increasing their potential for long-term successful realisation.
Keywords: Environmental Governance; agriculture; Agri-food system; Switzerland; UK; New Zealand